Cytokine secretion patterns distinguish herpes simplex virus type 2 meningitis from herpes simplex virus type 2 genital herpes - Bjerhem, Moa; Svensson, Alexandra; Studahl, Marie; Tunbäck, Petra; Boman, Eva-Marie; Brandström, Kenny; Lingblom, Christine; Reyahi, Azadeh; Thörn, Karolina; Eriksson, Kristina (Frontiers in Immunology, 2025)
The aim of this study was to identify immune factors that distinguish patients with herpes simplex virus type 2 (HSV-2) meningitis from patients with HSV-2 genital herpes by analyzing demographic data, in vitro production of cytokines and other immune factors secreted by patient peripheral blood mononuclear cells (PBMC), and existing antibody responses. PBMC and plasma were collected from patients previously diagnosed with HSV-2 meningitis (n=49) and HSV-2 genital herpes (n=38). PBMC were cultured in the presence or absence of HSV-2 and followed by multiplex analyses of culture supernatants for a panel of immune factors including Th1 and inflammatory cytokines, interferons, and chemokines. Plasma was analyzed for type-specific HSV antibodies and HSV-2 DNA. The multivariate method OPLS-DA was used to identify immune response patterns that differentiate the two patient groups. The multivariate analysis showed that the immune profile differed significantly between the two different HSV-2 disease manifestations. Meningitis patients were distinguished by the spontaneous production of several anti-viral immune factors by PBMC including type I and type III IFNs. PBMC from HSV-2 meningitis patients also secreted significantly higher levels of IFN-γ in response to HSV-2 compared to PBMC from HSV-2 genital herpes patients. Blocking the type I IFN receptor reduced the production of HSV-2-induced IFN-γ by PBMC suggesting that enhanced production of type I IFNs could promote IFN-γ recall responses. The levels of HSV-2 type-specific antibodies did not differ between the patient groups. In conclusion, we show that HSV-2 meningitis leads to a more profound activation of both innate and acquired PBMC immune responses, compared to that of HSV-2 genital herpes. Whether these differences are the cause, or the consequence, of the different disease manifestations remains to be determined.